Magnetic Moments of 70-Plet Baryons in Quark Model and QCD Sum Rules. (12th October 2015) - Aliev, T. M.; Zamiralov, V. S.
Abstract : Magnetic moments of the positive parity 70-plet baryons are estimated in the framework of the nonrelativistic quark model and QCD sum rules method. It is found that the magnetic moments of the 70-plet baryons can be expressed in terms of the F and D couplings and exhibit unitary symmetry. The QCD sum rules for the magnetic moments of the 70-plet octet baryons are formulated. A comparison of our results on magnetic moments of 56-plet and 70-plet baryons predicted from QCD sum rules is presented.